The structure of the AliC GH13 α‐amylase from Alicyclobacillus sp. reveals the accommodation of starch branching points in the α‐amylase family. Issue 1 (15th January 2019) - Agirre, Jon; Moroz, Olga; Meier, Sebastian; Brask, Jesper; Munch, Astrid; Hoff, Tine; Andersen, Carsten; Wilson, Keith S.; Davies, Gideon J.
Abstract : In the light of NMR data on product profiles, the structure of an Alicyclobacillus sp. CAZy family GH13 α‐amylase highlights the accommodation of branch points in the α‐amylase active centre. Abstract : α‐Amylases are glycoside hydrolases that break the α‐1, 4 bonds in starch and related glycans. The degradation of starch is rendered difficult by the presence of varying degrees of α‐1, 6 branch points and their possible accommodation within the active centre of α‐amylase enzymes. Given the myriad industrial uses for starch and thus also for α‐amylase‐catalysed starch degradation and modification, there is considerable interest in how different α‐amylases might accommodate these branches, thus impacting on the potential processing of highly branched post‐hydrolysis remnants (known as limit dextrins) and societal applications. Here, it was sought to probe the branch‐point accommodation of the Alicyclobacillus sp. CAZy family GH13 α‐amylase AliC, prompted by the observation of a molecule of glucose in a position that may represent a branch point in an acarbose complex solved at 2.1 Å resolution. Limit digest analysis by two‐dimensional NMR using both pullulan (a regular linear polysaccharide of α‐1, 4, α‐1, 4, α‐1, 6 repeating trisaccharides) and amylopectin starch showed how the Alicyclobacillus sp. enzyme could accept α‐1, 6 branches in at least the −2, +1 and +2 subsites, consistent with the three‐dimensional structures with glucosyl moieties in the +1 and +2 subsites and the solvent‐exposure of the −2 subsite 6‐hydroxyl group. Together, the work provides a rare insight into branch‐point acceptance in these industrial catalysts.